2018
DOI: 10.1097/iae.0000000000001755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Foveal Avascular Zone Area, Vessel Density, and Cystoid Changes in Diabetic Retinopathy

Abstract: The FAZ area and vessel density at the superficial capillary plexus level are reproducible and independent of the presence of cystoid edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…[ 49 62 ] It is important to point out that presence of CME may not influence the reproducibility and effectiveness of OCTA in the measurement of FAZ in SCP. [ 8 88 ] FAZ has been found to have no or the least correlation among other vascular indices with systemic indicators like HbA1c and duration of DM;[ 17 66 ] however, in one study, FAZ size was found to be correlated with HbA1c. [ 61 ] These should be confirmed in larger studies and considered in the design of studies and interpretation of results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 62 ] It is important to point out that presence of CME may not influence the reproducibility and effectiveness of OCTA in the measurement of FAZ in SCP. [ 8 88 ] FAZ has been found to have no or the least correlation among other vascular indices with systemic indicators like HbA1c and duration of DM;[ 17 66 ] however, in one study, FAZ size was found to be correlated with HbA1c. [ 61 ] These should be confirmed in larger studies and considered in the design of studies and interpretation of results.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 20 36 44 64 ] While interpreting the results, one should consider that the presence of CME may influence reproducibility and effectiveness of OCTA in the measurement of FAZ and vascular indices, particularly in DCP. [ 8 88 ] Eyes with DME that showed outer plexiform layer (OPL) disruption, loss of integrity of the DCP, larger FAZ area, and more MAs in DCP had poor response to anti-VEGF treatment. [ 36 ] Size of FAZ and VD did not change following IDI and anti-VEGF therapy but a reduction in the caliber of DCP vessels and an increase in CCCD was observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent evidence suggests that vessel density measurement of the DP may be influenced by the presence of coexisting macular edema due to the interference with image segmentation 27 28 while the SP vessel density may be independent of the presence of cystoid edema. 29 Technologic limitations of SS-OCTA, including increased variability with different axial lengths 30 and the impact of patient cooperation on image quality, introduce an intrinsic bias to our study that needs to be taken into account when drawing definitive conclusions.…”
Section: Concerning Qualitative Macroscopic Analysis Despite the Prementioning
confidence: 98%
“…; Tarassoly et al. ). However, at the time of this study, OCT angiography was not available and OCT algorithms measuring the macular capillary network in three dimensions remain in development.…”
Section: Discussionmentioning
confidence: 98%